Komparasi Karakteristik Pengusahaan dan Pendapatan Petani Karet Berwawasan Lingkungan dan Tradisional di Kabupaten Musi Banyuasin ( Comparison of Business Characteristics and Income of Environmentally and Traditional Rubber Farmers in Musi Banyuasin Regency) - Riswani Riswani; Yunita Yunita; Henny Malini; M. Naufal A.M (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Riswani R, Yunita Y, Malini H, Naufal AMM. 2019. Comparison of business characteristics and income of environmentally and traditionally rubber farmers in Musi Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 318-324. Palembang: Unsri Press. Rubber commodities in South Sumatra, even though they have been cultivated with land area that tends to be larger than other provinces, but have not been balanced with production and quality, which is still low, due to the methods of exploitation and processing that are not yet ideal and have no environmental impact. It makes the prices and market demand fluctuate with a downward trend. The purposes of this research were to describe the comparability of environmentally rubber farmer and traditional rubber farmer, then followed by an analysis of the factors that influence them so that recommendations for improvements must be made. The research was using survey method with two gruops of respondent, so that primary and secondary data were obtained, which were processed using structured tabulations, calculated using mathematical formulas and tested with statistical tools. The results showed that there were differences in the use of production inputs and processing of Bokar products by rubber farmers who are environmentally sound and who are still traditionally trying to have an impact on the differences in prices received and income obtained significantly. From the results of the factors testing that influence the income showed that only the selling price factor has a significant effect on farmer income, while the selling price tends to be linier with the quality of production, so improving production quality is a priority solution in an effort to increase the farmer income.Keywords: income farmer, quality, rubber